Where eighty-four languages were once spoken an account of Melaka 1400-1824 - DEVINDER RAJ (Devinder Raj, 2020)
In this short account of the history of Melaka, Devinder Raj weaves in letters, myths and oft-forgotten historical facts to craft an image of his home state during the Melakan sultanate and under the rule of the Portuguese, the Dutch and the British. Filling in the gaps in history textbooks, and piecing together accounts such as letters from Melaka's Tamil merchants to the King of Portugal and the proposed British effort to demolish Melaka entirely, Where Eighty-four Languages Were Once Spoken revisits the storied history of a historic city.